Lychnothamnus Barbatus (Meyen) Leonh. – Rediscovered In Shalow Lake Šventininkai (Lithuania) After 50 Years - Sinkevičiene, Zofija; Urbaitė-Maževič, Neringa (Biodiversity: Research and Conservation, 2012)
Lychnothamnus barbatus, which in Lithuania occurs northernmost in Europe, was identified in 4 lakes: Balsys, Mažasis Gulbinu, Vygris and Šventininkai. The aim of the paper was to present the recent vegetation, habitat conditions, abundance and co-occurring plant species in shallow Lake Šventininkai. L. barbatus population was rediscovered after 50 years. It was recorded in 1823 and 1960, but it has not been detected later on during scattered investigations until now. Recent vegetation of Lake Šventininkai is a typical of eutrophic lakes with the domination of Ceratophyllum demersum, Elodea canadensis and rarely - L. barbatus. The submerged communities are represented by 7 associations. L. barbatus was distributed at the depth of 1.1-2.1 m. Nitellopsis obtusa, Chara globularis, Chara contraria were the most common, co-occurring species of I. barbatus. Lake Šventininkai is a unique, very shallow (average depth <3 m) lake with re-established L. barbatus population after its total decline in strongly polluted lake waters following the lake’s self-purification. The presented data are important for the restoration of the status of the protected area and management of this territory.